Generation and Function of Non-cell-bound CD73 in Inflammation - Schneider, Enja; Rissiek, Anne; Winzer, Riekje; Puig, Berta; Rissiek, Björn; Haag, Friedrich; Mittrücker, Hans-Willi; Magnus, Tim; Tolosa, Eva (Frontiers in Immunology, 2019)
Extracellular adenine nucleotides participate in cell-to-cell communication and modulate the immune response. The concerted action of ecto-nucleotidases CD39 and CD73 plays a major role in the local production of anti-inflammatory adenosine, but both ecto-nucleotidases are rarely co-expressed by human T cells. The expression of CD39 on T cells increases upon T cell activation and is high at sites of inflammation. CD73, in contrast, disappears from the cellular membrane after activation. The possibility that CD73 could act in trans would resolve the conundrum of both enzymes being co-expressed for the degradation of ATP and the generation of adenosine. An enzymatically active soluble form of CD73 has been reported, and AMPase activity has been detected in body fluids of patients with inflammation and cancer. It is not yet clear how CD73, a glycosylphosphatidylinositol (GPI)-anchored protein, is released from the cell membrane, but plausible mechanisms include cleavage by metalloproteinases and shedding mediated by cell-associated phospholipases. Importantly, like many other GPI-anchored proteins, CD73 at the cell membrane is preferentially localized in detergent-resistant domains or lipid rafts, which often contribute to extracellular vesicles (EVs). Indeed, CD73-containing vesicles of different size and origin and with immunomodulatory function have been found in the tumor microenvironment. The occurrence of CD73 as non-cell-bound molecule widens the range of action of this enzyme at sites of inflammation. In this review, we will discuss the generation of non-cell-bound CD73 and its physiological role in inflammation.